Molecular characterization of Escherichia coli isolated from different food sources - Cheah, Yoke Kqueen; Tay, Lee Wen; Azmi, Aida Azrina; Radu, Son; Nakaguchi, Yoshitsugu; Nishibuchi, Mitsuaki (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2015)
Escherichia coli and Escherichia coli O157 were identified from "selom" (Oenanthe stolonifera), "pegaga" (Centella asiatica), beef, chicken, lamb, buffalo, "ulam Raja" (Cosmos caudatus) and "tenggek burung" (Euodia redlevi). The bacteria were recovered using chromagenic agar. Isolated Escherichia coli and Escherichia coli 0157 were further characterized by plasmid profiling and enterobacterial repetitive intergenic consensus-polymerase chain reaction (ERIC-PCR). The virulence genes of the isolates (VT1, VT2, LT, ST, eaeA, inV) that produces pathogenic Escherichia coli and 16S rRNA gene were screened by a multiplex PCR assay. The plasmid profiling analysis showed that out of 176 isolates, only 103 isolates contained plasmids. ERIC-PCR analysis generated amplified products in the range of ~150 bp to > 1000 bp categorizing isolates into a total of 52 different profiles. Multiplex PCR showed that 20 (32.3%) of the isolates carried eaeA gene, 6 (9.7%) isolates possessed inV genes, only 1 (1.6%) have VT2 genes and 1 (1.6%) as well carried VT1 genes, 2 (3.2%) of the isolates harboured LT genes, and only 1 (1.6%) isolate possessed ST genes. There were no correlation between plasmid, ERIC-PCR and virulence genes profiles.